Early-onset catatonia associated with SHANK3 mutations: looking at the autism spectrum through the prism of psychomotor phenomena - Dhossche, Dirk; de Billy, Clément; Laurent-Levinson, Claudine; Le Normand, Marie T.; Recasens, Christophe; Robel, Laurence; Philippe, Anne (Frontiers in Psychiatry, 2023)
Individuals with Phelan-McDermid syndrome (PMS) present with a wide range of diagnoses: autism spectrum disorder, intellectual disability, or schizophrenia. Differences in the genetic background could explain these different neurodevelopmental trajectories.However, a more parsimonious hypothesis is to consider that they may be the same phenotypic entity. Catatonic disturbances occasionally reported from adolescence onwards in PMS prompts exploration of the hypothesis that this clinical entity may be an early-onset form of catatonia. The largest cohort of children with childhood catatonia was studied by the Wernicke-Kleist-Leonhard school (WKL school), which regards catatonia as a collection of qualitative abnormalities of psychomotricity that predominantly affecting involuntary motricity (reactive and expressive).The aim of this study was to investigate the presence of psychomotor signs in three young adults carrying a mutation or intragenic deletion of the SHANK3 gene through the prism of the WKL school conception of catatonia.This study was designed as an exploratory case study. Current and childhood psychomotor phenomena were investigated through semi-structured interviews with the parents, direct interaction with the participants, and the study of documents reporting observations of the participants at school or by other healthcare professionals.The findings show catatonic manifestations from childhood that evolved into a chronic form, with possible phases of sub-acute exacerbations starting from adolescence, leading to the diagnosis of early-onset catatonia.Qualitative abnormalities of psychomotor function are important for the differential diagnosis between autism and catatonia. The presence of catatonic symptoms from childhood associated with autistic traits leads us to consider that this singular entity fundamentally related to SHANK3 mutations could be a form of early-onset catatonia. Further case studies Additional cases are needed to describe the singular semiology of such individuals and confirm our observations.